Hyper‐Raman and Raman scattering in paratellurite TeO2. (4th February 2013) - Rodriguez, Vincent; Couzi, Michel; Adamietz, Frédéric; Dussauze, Marc; Guery, Guillaume; Cardinal, Thierry; Veber, Philippe; Richardson, Kathleen; Thomas, Philippe
Abstract : Raman spectra of the tetragonal D 4 4 structure of paratellurite TeO2 have been revisited avoiding anomalous polarization‐selection‐rules violations previously observed and due to optical activity. We present a complementary hyper‐Raman scattering study of paratellurite. Wavenumber and symmetry assignments are given for all expected 21 Raman active optical branches, except one LO component (out of the eight expected TO–LO pairs) of the polar doublet E modes. Also, the four expected hyper‐Raman active A2 (TO) modes have been observed. Moreover, we have observed a strong Kleinman‐disallowed hyper‐Rayleigh signal, which is tentatively assigned as a first evidence of hyper‐Rayleigh optical activity. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : We present for the first time a hyper‐Raman scattering study of paratellurite. We have also revisited the Raman spectra of paratellurite. Anomalous polarization‐selection‐rules violations previously observed in Raman and due to optical activity are possible to avoid when light propagates at 45° of the O x and O y optical axes. From this single crystal study, all expected optical phonon modes frequencies and symmetries are given, except one E (LO) mode that could not be observed. We have evidenced a strong harmonic light scattering signal in the ZY ′ Y ′ spectrum that we tentatively assigned to hyper‐Raleigh optical activity that comes from a mixed dipolar electric–magnetic effect.